Disproportionate preponderance of HPV genotypes associated with anogenital warts among HIV-positive MSM - Borena, Wegene; Kitchen, Maria; Gisinger, Martin; Taylor, Ninon; Oberkofler, Hannes; Dewasurendra, Diyani; Widschwendter, Andreas; Stoiber, Heribert; von Laer, Dorothee; Sarcletti, Mario (Frontiers in Public Health, 2024)
Background In this study, we characterized the HPV genotype distribution in a population of 489 adults already positive for HPV DNA. The study population was divided into two groups: 244 HIV-positive (HIV+) men who have sex with men (MSM) undergoing routine anal screening for sexually transmitted diseases (STDs) and 245 women undergoing routine cervical cancer screening. Acknowledging the fact that women and MSM represent two independent circles of sexual practices, which are—largely—exclusive of each other, we were interested in determining if particular genotypes of human papillomavirus (HPV) disproportionately predominate in one of these circles compared to the other. Results HIV+ MSM are significantly more likely to be infected with multiple genotypes at a time, with an odds ratio (OR) of 9.30 (95% confidence interval [CI]: 3.91–22.1) and a p-value of <0.001. In addition, multivariable-adjusted logistic regression analysis showed that anal swab samples were significantly more likely to harbor lrHPV infections, with an OR of 6.67 (95% CI: 2.42–18.4) and a p-value of <0.001, in particular, HPV 6, with an OR of 8.92 (95% CI: 3.84–20.7) compared to cervical samples of screening women. Conclusion Given the significant impact of recurrent anogenital warts (AGWs) on quality of life and the accompanying predisposition to invasive anal cancer, our data underscore the critical need for HPV vaccination. This includes expanding vaccination eligibility to include both boys and adults within high-risk populations.